PROTECTING PERSONAL DATA IN THE AGE OF ARTIFICIAL INTELLIGENCE: CHALLENGES AND SOLUTIONS (Lex localis - Journal of Local Self-Government, 2025)
The world is currently experiencing advanced technological conditions, where artificial intelligence (AI) is increasingly used in various aspects of life. One of the critical issues raised by this new technology is the protection of individuals' personal data. Despite the benefits of AI, it can pose a threat to the privacy and personal security of individuals. Thus, in anticipation of enforcing Law No. 18-07 concerning the protection of natural persons in the processing of personal data, starting from August 2023, this research paper aims to highlight the most important legal measures adopted by legislators to protect personal data. There must be a balance between benefiting from AI and protecting personal data, which can only be achieved through legal intervention. The findings from studying this topic suggest that protecting personal data amidst increased AI usage requires comprehensive cooperation between the public and private sectors, in addition to providing necessary legislation and enhancing public awareness.